HR 2021
DOI: 10.20517/2394-5079.2021.07
|View full text |Cite
|
Sign up to set email alerts
|

Effect of mesenchymal stem cell in liver regeneration and clinical applications

Abstract: Liver disease accounts for approximately 2 million deaths per year worldwide with cirrhosis, viral hepatitis, and malignancy being the most common causes. Consequently, the regenerative capacity of the liver is a topic of extreme interest in the search for curative therapies to end-stage liver disease. Mesenchymal stem cells (MSCs) have emerged as a promising new therapy for hepatic regeneration. MSCs have multiple properties that make them an appropriate treatment option for liver disease including easy acces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 134 publications
0
5
0
1
Order By: Relevance
“…Based on self-renewal potential and differentiation ability in hepatocyte-like cells researches using animal models of carbon tetrachloride and α-galactosylceramide toxic liver injuries have proved the favorable effect of MSCs on function and liver damage (Alfaifi et al, 2018;Wang et al, 2018). Mesenchymal stem cells based therapy has been advanced as a substitute for liver transplantation, especially in alcoholic and viral cirrhosis, but has not yet surpassed the early phases of clinical studies (Lee et al, 2021). To date, no clinical trials have been conducted to evaluate the effects of MSCs in DILI.…”
Section: Discussionmentioning
confidence: 99%
“…Based on self-renewal potential and differentiation ability in hepatocyte-like cells researches using animal models of carbon tetrachloride and α-galactosylceramide toxic liver injuries have proved the favorable effect of MSCs on function and liver damage (Alfaifi et al, 2018;Wang et al, 2018). Mesenchymal stem cells based therapy has been advanced as a substitute for liver transplantation, especially in alcoholic and viral cirrhosis, but has not yet surpassed the early phases of clinical studies (Lee et al, 2021). To date, no clinical trials have been conducted to evaluate the effects of MSCs in DILI.…”
Section: Discussionmentioning
confidence: 99%
“…Such unpredictable results were even exacerbated by inconsistent and frequently poorly effective maturation protocols performed ex vivo, aimed to generate different somatic cells, including liver cells. Over the years, several researchers and biotech companies have proposed MSCs as multipotent alternative solution to tissue-resident progenitor liver cells, bounded by genetic and epigenetic instabilities, but even more, limited by hepatic maturation level and bio-synthetic activities [ 22 ].…”
Section: Extraembryonic Mscmentioning
confidence: 99%
“…However, more than 2 × 10 8 MSCs reduced liver damage in patients with liver cirrhosis [ 121 ]. In most clinical studies, one-time doses were administrated, but had no significant difference in treating liver cirrhosis compared with two doses a month apart [ 122 ]. Nevertheless, most clinical trials have shown that MSC-based therapies have beneficial effects on liver fibrosis ( Table 2 ).…”
Section: Mscs-based Clinical Application For Liver Diseasementioning
confidence: 99%